Актуальність SOFT SKILLS в процесі професійного розвитку співробітників та управління змінами компанії - Шевчук, О.Ю.; Агеєва, Ірина Вікторівна; Ahieieva, Iryna (Мелітополь, ТДАТУ, 2021)
UKR : В статті розглянуті поняття soft skills та hard skills та їх значущість для розвитку спеціалі ста в професійній сфері. Надані ключові характеристики «м’яких» та «твердих» компетенцій. Проведений контент аналіз дефініцій «soft skills» и «hard skills»,відмічені загальні та відмінні риси в підходах./////// ENG: The article considers the concepts of soft skills and hard skills and their significance for the development of a specialist in the professional field. Key characteristics of "soft" and "hard" competencies are provided. The content analysis of definitions "soft skills" and "hard skills" is carried out, the general and distinctive features in approaches are noted. On the principle of indivisibility of hard and soft skills the specificity of training in business is built. Some companies rely on soft skills when recruiting, realizing that a person who can learn quickly will grasp the necessary skills on the fly. Other companies first focus on technical skills, realizing that a person will be able to develop soft skills in the process of work, performing tasks and implementing projects [2]. Each author considers and defines the concepts of "soft skills" and "hard skills" in their own way. But all definitions are partially interconnected, some of them are intertwined with each other. Soft skills are related to communication skills that are necessary for successful work in professional activities. Hard skills are the ability to perform certain tasks that can be clearly demonstrated. Currently, there are many models of soft skills, but they have not only differences but also similarities. For example, many re searchers consider communication skills, decision-making, and time management to be mandatory elements of the model. Undoubtedly, the influence of the formed "soft skills" and "hard skills" and the constant development of soft and hard competencies for the successful achievement of goals, competent use of skills, knowledge and abilities in profes sional activities and to achieve competitiveness in the labor market.
Relevance of soft skills in the process of professional development of employees and change management of the company
Keywords: розвиток компетенцій; soft skills; hard skills; моделі soft skills; емоційна компетентність; розвиток персоналу; soft skills models; competence development; hard skills; emotional competence; staff development; competence development